Pengaruh Pemberian Ekstrak Daun Alpukat (Persea Americana Mill.) terhadap Daya Ingat Mencit Jantan dengan Metode Labirin Y-Maze - Meyliawati, Ika; Ardiyantoro, Bagas; Jayak Pratama, Kharisma (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Memory is a vital biological system in the body that plays a role in storing, processing, and recalling information. Over time, due to aging or external factors, memory function may decline. One possible effort to maintain and improve cognitive performance is through the use of bioactive compounds with antioxidant properties. Avocado (Persea americana Mill.) leaves contain flavonoids, which act as antioxidants and possess neuroprotective effects that may enhance cognitive function, including memory. This study aimed to determine the effect of avocado leaf extract on the memory of male mice and to identify the most effective dose in improving cognitive performance. The extract was obtained using the maceration method with 70% ethanol as the solvent. Memory activity was tested on male mice, which were divided into five groups: negative control, positive control, and three treatment groups given avocado leaf extract at doses of 50, 100, and 200 mg/kgBW. The Y-Maze method was employed to assess memory through two parameters: latency time and error numbers. The results demonstrated that avocado leaf extract significantly improved memory in the test animals. Mice induced with 10% ethanol showed an increase in latency time and error numbers, while the groups treated with avocado leaf extract experienced reductions in both parameters. The most effective dose was 200 mg/kgBW, which produced a latency time difference of 19.5 seconds and an error number difference of 3.57. Therefore, avocado leaf extract shows potential as a natural agent to support and enhance cognitive function.